Soil Nitrogen Supply Linking Plant Available N to Ecosystems Functions and Productivity - Dessureault-Rompré, Jacynthe (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book, a printed edition of the Special Issue Soil Nitrogen Supply: Linking Plant Available N to Ecosystem Functions and Productivity, presents thoughtful research papers that will advance our understanding of this fascinating topic. New knowledge about modeling and the impact of cover crops, crop residues, soil amendment, and other management practices is presented in the context of agricultural and urban ecosystems.